A mixed rebalancing strategy in bike sharing systems. Issue 7 (3rd July 2022) - Xu, Guoxun; Xiang, Ting; Li, Yanfeng; Li, Jun; Guo, Qiang
Abstract : In a bike sharing system (BSS), for various reasons, such as truck fuel load, truck capacity and high customer demand, the number of trucks deployed by the BSS operator is usually insufficient and they cannot balance all of the stations in time. To incentivize users to relocate some of the excess bikes from stations with surplus bikes to bike deficient stations, a mixed rebalancing strategy is proposed. The problem is formulated as a mixed-integer linear programming model. A hybrid genetic algorithm is developed to solve the proposed problem. Computational experiments are performed to illustrate the properties of the problem. The numerical results show that the proposed solution method can yield high-quality solutions in short computing times.